Factors Influencing Preeclampsia In Pregnant Women: Literature Review - Jannah, Zahrotul; Rahmawati, Alfiah (Jurnal Maternitas Kebidanan, 2025)
Introduction: Preeclampsia is a pregnancy complication characterized by hypertension and proteinuria. This disease typically manifests at a gestational age exceeding 20 weeks. Preeclampsia may result in maternal mortality. Preeclampsia is influenced by multiple variables, including a history of hypertension, obesity, lifestyle habits, exposure to tobacco smoke, and caffeine intake. This study aimed to discover the factors influencing preeclampsia in pregnant women.Method: The method used in the study was a literature review by analyzing literature published in scientific journals registered with Google Scholar and PubMad from 2020-2024. Results:13 articles have revealed that factors associated with the incidence of preeclampsia include a history of hypertension, obesity, exposure to cigarette smoke, caffeine consumption, and balanced nutrition.Conclusion:Factors influencing the incidence of preeclampsia include a history of hypertension, obesity, exposure to tobacco smoke, caffeine use, and nutritional balance.Suggestion:the factors that cause preeclampsia that have been discovered can be used to prevent and overcome the problem of preeclampsia in pregnant women.